Physical and psychosocial factors associated with depression among adults with type 2 diabetes mellitus at a Federally Qualified Healthcare Center. (26th November 2018) - Lee, Joohee; Brazeal, Michelle; Choi, Hwanseok; Rehner, Tim A.; McLeod, Stephanie T.; Jacobs, Christina M.
ABSTRACT: Purpose: The purpose of this study is to examine the prevalence of depression and physical and psychosocial factors associated with depression among adults with Type 2 Diabetes Mellitus (T2DM). Methods: The sample included 421 patients with T2DM at a Federally Qualified Healthcare Center in a southern state. The Patient Health Questionnaire (PHQ-9) was used to measure the severity of depression. Results: The multiple logistic regression analyses revealed that the likelihood of depression increased as the level of pain increased and as the level of ambulation difficulties increased. The likelihood of depression increased as the number of traumatic events increased and as the number of SES-related stressors increased. Expectedly, the likelihood of depression decreased as levels of self-esteem increased. Conclusions: The findings support that health care providers developing care plans for individuals with diabetes need to include assessments and interventions that address both the physical and psychosocial needs of patients.